Use of CO2Laser in Treatment of Oral Irritation Fibroma Adjacent to Implant: A Case Report - Abdolrahim Davari; Farzad Ziaei (Isfahan University of Medical Sciences, 2021)
Nowadays laser can be used in many dental procedures. Some of the advantages of laser surgery in oral soft tissue lesions treatment are: reduced need to use local anesthesia, minimal bleeding, faster healing and reduced risk of post-operative complications. Due to above reasons laser was used for treatment of this irritation fibroma case.Case Report:In this case report an irritation fibroma lesion in a 54 year old female was removed by CO2laser surgery and the rate and quality of healing and patient's relief levels have been evaluated